Homoeopathic Treatment of Mild Cases of COVID-19 on Home Isolation: A Retrospective Observational Study - Balakrishnan, Thankaraj; Thomas, Rekha; Mathew, George; Rajesh, Anu; Jain, Saurabh Kumar; Agarwal, Radhika; Kapoor, Anu (Homœopathic Links, 2023)
While the world grappled with the pandemic of coronavirus disease 2019 (COVID-19), medical fraternity and policy makers tried desperately to control its spread in the absence of any definite treatment protocol. The scope of homoeopathy, which has been historically found effective in epidemics, has been investigated in the present study. This study was conducted to evaluate the effect of individualised homoeopathic medicine on mild cases of COVID-19 under home isolation. A retrospective, single-arm, non-randomised, open-label, observational trial was conducted on 185 laboratory confirmed mild cases of COVID-19 at Nehru Homoeopathic Medical College and Hospital, Delhi, during September to December 2020. Complete symptom resolution days was the primary outcome (from baseline to total zero symptom score); while assessment of severity of each symptom and sign on a scale of 0-3 ( 0- absent, 1-mild. 3- severe), at baseline and Day 14 comprised of the secondary outcome. Intention-to-treat sample (n = 185) was analysed with SPSS IBM version 20. Of all the patients (n = 185), 165 (90%) successfully completed the follow-up period. The mean (interquartile range [IQR]) age was 35 (26–45) years; the male: female ratio was 11:9.2. Fever (56%), cough (54%), fatigue (45%) and sore throat (36%) were the most common symptoms reported. Median (IQR) time for resolution of symptoms was 4 (3–8) days. Sixty-eight per cent patients recovered within 6 days and rest within 7 to 14 days. The most prescribed medicines were Bryonia alba (30%), Arsenicum album (25%) and Pulsatilla nigricans (12%) accounting for 67% of the total medicines. This study, though preliminary, revealed a positive treatment effect of individualised homoeopathic medicines in promptly alleviating the symptoms of mild COVID-19. Randomised controlled trials with greater scientific rigour are warranted.
Keywords: COVID-19; home isolation; homoeopathy; symptom resolution days; Bryonia alba